DEVELOPING DRAOMAI APPLICATION AS INDONESIAN LANGUAGE LEARNING MEDIA OF DRAMA TEXT MATERIAL FOR GRADE VIII JUNIOR HIGH SCHOOL STUDENTS - Syefira Prihapsari Syefira Prihapsari; Ari Kusmiatun Ari Kusmiatun (LPPM Universitas Widya Dharma, 2023)
This research aims to: (1) describe the process of developing draomai application as Indonesian language learning media of drama text material for grade VIII junior high school students and (2) describe the feasibility of developing a draomai application product as Indonesian language learning media of drama text material for grade VIII junior high school students. The research method used is Research and Development (R&D) with the ADDIE model. The research was conducted in stages, including (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The assessment of media was carried out by two material experts, media experts, and teachers to determine the feasibility of the media. The student response test involved students from class VIII C of SMP Negeri 4 Depok which was accomplished online and offline. The data collection technique used was a questionnaire. Then, the data analysis technique used was mixed methods, that are qualitative to analyze the questionnaire and quantitative to process the numeric data in the form of test scores. The results showed that validation from material experts and media experts has an average score of 4.6 and 4.3 which are categorized as very feasible. Furthermore, the feasibility level obtained from the teacher's assessment showed an average score of 5 with a very feasible category. Meanwhile, based on the average response results from students, it showed a final average score of 4.4 points that is categorized as very feasible.